Nilai parameter wisata pesisir Pulau Sagori pada zona pemanfaatan umum - Afyudi, Bobby; Nurdiana A; Mansyur, Akhmad (Jurnal Sosial Ekonomi Perikanan, 2023)
Sagori island has scoped in Common Utilization Zone as it mention in document of Plan of Coastal and Small Islands Zonal Area known as RZWP3K and put on sub zonation of coastal tourism. On the other side, Sagori Island has been set into a high level of anthropogenic which can cause its own ecologic and social-economic disturbed. It needs a futher step of study about giving a valui on tourism parameters at coastal of Sagori Siland. This study is about giving valuea to the 7 parametters based of its determined. Those parameters are Originality and naturalness, Uniqueness, Size of Area, Nature Beauty, Natural Amenity, Accessibility and Historical Value. Most of the parameter values show that there is suitability between the coastal state and the value has been given. This study also is to exhibit of major potential of economic growth by developing the tourism sector as also giving an added value to the coastal zone. Thus, there will be a well-needed of a good co-management system between all concerned stakeholders to bring that on a table.